Leaderless RiPPs expand the repertoire of fungal secondary metabolites - Sung Chul Park; Livia D. S. Oster; Jacob Golan; Jillian Myers; Anne Pringle; Milton T. Drott; Nancy P. Keller (Proceedings of the National Academy of Sciences, 2026)
Ribosomally synthesized and post-translationally modified peptides (RiPPs) are secondary metabolites produced by bacteria, plants, animals, and fungi. Canonical fungal RiPP precursors possess a leader sequence cleaved during maturation. The first RiPPs described in fungi were the MSDIN-derived peptides responsible for the toxicity of lethal Amanita mushrooms. In this study, we upend the conventional understanding of fungal RiPPs, discovering a subclass that has diversified and lacks a leader sequence, an empirical example of leaderless RiPPs in fungi. We use a combinatorial analysis of NMR and MS/MS with an updated bioinformatic pipeline to pair MSDIN genes to leaderless peptides in Amanita phalloides , a European species spreading in California. Leaderless MSDIN transcripts are expressed several orders of magnitude more than most canonical MSDINs, with significantly higher expression in invasive populations. Our results redefine the understanding of fungal RiPP architectures and suggest differential regulation of non-canonical RiPPs may contribute to the invasion biology of the world’s deadliest mushroom.